The New Old Legal Realism - George, Tracey E. (2011)
Do the decisions of appellate courts matter in the real world? The American judicial system, legal education, and academic scholarship are premised on the view that they do. The authors want to reexamine this question by taking the approach advocated by the original Legal Realists. The current project seeks to add to our knowledge of the relevance of case law by focusing on an area that has received little examination: how pronouncements about employment discrimination law by appellate courts translate into understandings and behavior at the ground level. As our lens, we use evidence of how people talk about the relevance of changes in the law. This new Old Legal Realist perspective suggests that social and economic factors play a more important role than case law in outcomes on the ground. Cases cannot have an impact, if the local social and economic variables are not aligned in a fashion that allows the impact to occur